1977
DOI: 10.1073/pnas.74.9.3869
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight peptide inhibits RNA synthesis in human leukemic and phytohemagglutinin-stimulated leukocytes and globin mRNA transcription in differentiating Friend cells.

Abstract: The RNA synthesis of human leukemic leukocytes and phytohemagglutinin-stimulated lymphocytes is markedly reduced by administration of a low-molecular-weight nonhistone peptide factor from calf thymus. Treatment with the factor strongly inhibits hemoglobin production and globin mRNA transcription in dimethyl sulfoxide-stimulated Friend cells without appreciably modifying the rate of cell growth. Evidence for specificity of these effects is provided by the lack of action of the factor on both growth rate and RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…They show very high inhibition activity on chromatin-directed or DNA-directed RNA synthesis in vitro (Gianfranceschi, Amici & Guglielmi, 1976). Moreover, treatment with the peptides strongly inhibits the RNA synthesis of human leukaemic leukocytes and phytohemagglutinin-stimulated lymphocytes (Amici, Rossi, Cioe, Matarese, Dolei & Gianfranceschi, 1977). This report shows that the DNA-binding peptides are able to slow down the rate of DNA and RNA synthesis in the L1210 mouse leukaemia cells maintained continuously in vitro (Table 1).…”
mentioning
confidence: 74%
“…They show very high inhibition activity on chromatin-directed or DNA-directed RNA synthesis in vitro (Gianfranceschi, Amici & Guglielmi, 1976). Moreover, treatment with the peptides strongly inhibits the RNA synthesis of human leukaemic leukocytes and phytohemagglutinin-stimulated lymphocytes (Amici, Rossi, Cioe, Matarese, Dolei & Gianfranceschi, 1977). This report shows that the DNA-binding peptides are able to slow down the rate of DNA and RNA synthesis in the L1210 mouse leukaemia cells maintained continuously in vitro (Table 1).…”
mentioning
confidence: 74%
“…A possible explanation is that the corrective effect obtained on the cataract of old dog by means of wheat sprout treatment is due to a synergic effect among antioxidant molecules and other compounds, such as specific phosphorylated regulatory factors including the previously described acidic peptides (Amici et al 1983). These acidic peptides associate the action of the thymus and its extracts to WESPRE on recovering aging altered parameters.…”
Section: Discussionmentioning
confidence: 97%
“…Other liver age-related modifications, such as the increased volume and number of tetraploid nuclei, can be corrected by grafting a neonatal thymus into old mice (Pieri et al 1980;Pieri et al 1982). Results similar to those obtained by grafting a neonatal thymus have been achieved using mice treated with the calf thymus extract (TME) (Rossolini et al 1992;Basso et al 1993) Old rats treated with TME, prepared and characterized on the basis of non-immunological test, are capable of recovering altered glycogen and lipid levels, RNA/DNA ratio and transcriptional activity of RNA polymerase DNA-dependent in the liver (Gianfranceschi et al 1974;Gianfranceschi et al 1975;Amici et al 1983).…”
Section: Introductionmentioning
confidence: 91%
“…Their affinity for DNA is pH-dependent and is lower at alkaline pHs [1,2]. We previously reported that this class of peptides is able to inhibit RNA transcription in cells and in vitro reconstituted systems and to decrease cell growth of several tumour cell lines [3,4]. The removal of this fraction by alkaline buffer from the DNA of normal cells increases the DNA template capacity, but this effect is practically absent for the DNA of several cancer cell lines [5].…”
Section: Introductionmentioning
confidence: 99%